Pengembangan Teknologi Tepat Guna Pengolahan Sampah untuk Mendukung Desa Mandiri Budaya Berkelanjutan di Panggungharjo: Development of Waste Processing Technology to Support a Sustainable Independent Cultural Village in Panggungharjo - Setiawan, Wisnu; Putra, Hijrah Purnama; Wibowo, Afif Ari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Panggungharjo Village, located in Sewon Subdistrict, Bantul Regency, Special Region of Yogyakarta, holds a strategic position due to its cultural significance within Yogyakarta's special status. The village leverages this position to develop Kawasan Karangkitri as an integrated hub for artistic, tourism, economic, and environmental activities. Aligned with its status as an Independent Cultural Village (Desa Mandiri Budaya), the initiative aims to create a sustainable rural environment, enhance community welfare, and contribute to achieving the Sustainable Development Goals (SDGs). This community service program focuses on organic waste management through appropriate technology and community empowerment. A key innovation is the development of a compost block-making machine, which not only enhances waste processing efficiency but also adds economic value to the final compost product. Collaboration among the village government, community members, and academics from Universitas Muhammadiyah Surakarta and Universitas Islam Indonesia has been instrumental in providing skills training and intensive support for organic waste management. The program's outcomes include increased community capacity in environmental management, the emergence of new economic opportunities through compost-based enterprises, and the preservation of social and cultural characteristics. By introducing innovative waste management practices and emphasizing local wisdom, this initiative supports the village's transition into a sustainable tourism destination. With synergy between technology and the community, Panggungharjo Village aspires to be a competitive model of rural development that balances local traditions and innovation, contributing to environmental regeneration and resilience.